Public DNS System and Global Traffic Management - Huang, Cheng; Maltz, Dave; Li, Jin; Greenberg, Albert (INFOCOM, 2011 Proceedings IEEE, Shanghai, P.R. China, 2011)
Cloud service providers operate data centers around the world, and they depend on Global Traffic Management systems to direct requests from clients to the most appropriate data center to serve the requests. While GTM systems have been in-use for years, they are attracting re-newed interests due to the rapid expansion of cloud service providers' networks, the introduction of public DNS systems, as well as new proposals to alter how they should work and what information local DNS servers (LDNS) should make available to drive the GTM systems. This paper uses large-scale measurements conducted from more than 5M clients to establish properties of the current Internet that affect the design of the GTM systems, such as the stretch between a client's actual position and its LDNS from GTM's perspective, the impact of public DNS systems, and the granularity at which GTM decisions should be made. The results can inform the debate over how GTM systems should be designed.